1991
DOI: 10.1007/978-94-011-3792-8_8
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dimorphism in Sebastes

Abstract: Sexual dimorphism and factors that may cause it were investigated in 34 species of the genus Sebastes. Sexual dimorphism in standard length and morphometric characters are fairly common in rockfish. In many species males are shorter than females. However in males head length, width of orbit, interorbital width, length of upper jaw, longest pectoral fin ray and longest dorsal spine tend to be larger at a specified size than in females. Water-column species tend to be more dimorphic than demersal species. We sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 10 publications
2
12
0
Order By: Relevance
“…This is in contrast to most other Scorpaeniformes, females being often larger than males (Wyllie Echeverria 1986; Lenarz and Wyllie Echeverria 1991).Generally, it is rather common in fish that a larger size in females increase their fecundity, while the same may not be true in males (Berglund et al 1986). In the case of S. notata, the documented low fecundity (Muñoz et al 2005), compared to other Scorpaeniformes, such as Trigla lyra (Muñoz 2001) or H. dactylopterus (Muñoz and Casadevall 2002), could be the reason of the absence of sexual size dimorphism.…”
Section: Discussionmentioning
confidence: 81%
“…This is in contrast to most other Scorpaeniformes, females being often larger than males (Wyllie Echeverria 1986; Lenarz and Wyllie Echeverria 1991).Generally, it is rather common in fish that a larger size in females increase their fecundity, while the same may not be true in males (Berglund et al 1986). In the case of S. notata, the documented low fecundity (Muñoz et al 2005), compared to other Scorpaeniformes, such as Trigla lyra (Muñoz 2001) or H. dactylopterus (Muñoz and Casadevall 2002), could be the reason of the absence of sexual size dimorphism.…”
Section: Discussionmentioning
confidence: 81%
“…The greater distance between the pelvic and anal fi ns in females, differing from the other sexually dimorphic characters above, is considered to be related to fecundity and egg volume. Among the sexually dimorphic characters discussed by Lenarz and Wyllie Echeverria (1991), interorbital width, upper jaw length, pectoral fi n length, and longest dorsal fi n spine were not sexually dimorphic in S. owstoni. To further understand the factors related to sexually dimorphic characters, further species examination and detailed ecological studies are needed.…”
Section: Discussionmentioning
confidence: 87%
“…Wyllie Echeverria (1986) also suggested that males matured younger than females, thereby having a greater number of mating opportunities. However, Lenarz and Wyllie Echeverria (1991) subsequently reported that both sexes matured at the same age in many species, noting that the increased spawning opportunity hypothesis for early maturing males did not hold for all species. Applicability of the foregoing hypothesis to S. owstoni requires an investigation of age, growth, and age of maturity for that species.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations